The African Shipping Sector, the Need for and Means to Achieve Effective Cyber Risk Management - Myers, Chris (Scientia Militaria - South African Journal of Military Studies, 2023)
The African shipping sector is a significant enabler of trade within Africa and trade between Africa and the world. African countries are sourcing and integrating technical solutions from foreign suppliers and service providers within their maritime domain. Such technologies are embedded within and enable functionality within transportation systems, port and navigation infrastructure, telecommunications infrastructure, downstream oil and gas infrastructure, and various national defence and security systems. Unfortunately, while providing the required functionality, these technical solutions create security vulnerabilities that place the African shipping sector and national interests at risk if security within the maritime cyber domain is taken for granted. The study on which this article is based firstly sought to identify and deconstruct the technology and associated vulnerabilities within the African maritime domain. Secondly, the research attempted to determine how national strategy and policy could be used to manage these security vulnerabilities to raise awareness of maritime cybersecurity in the context of the African shipping sector and propose pragmatic steps to achieve it.